Online clearance measurement in high-efficiency hemodiafiltration - Gross, M.; Maierhofer, A.; Tetta, C.; Sénecal, L.; Canaud, B. (Kidney international, 2007)
The measurement of ionic dialysance by conductivity variation is an established method in diffusive hemodialysis. To extend the validity of this method for use in highly convective therapies, such as online hemodiafiltration, we derived a new model for the measurement of ionic dialysance. This method was validated in a study involving 12 patients on pre- and postdilution online hemodiafiltration under various conditions. Clinically, there was a very good agreement between the dialysance determined by conductivity variation and blood side urea clearance. Neither the dilution modes nor the flow rate of the substitution fluid was found to significantly influence this agreement. Our results show that ionic dialysance can be easily and precisely measured by conductivity variation, and this provides an excellent surrogate for urea clearance even in highly convective therapies.